2020
DOI: 10.1111/exd.14210
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the hair follicle canal for hair shaft emergence

Abstract: The emergence of hair is a defining event during mammalian skin development, but the cellular mechanisms leading to the opening of the hair follicle canal remain poorly characterized. Our previous studies have shown that early hair buds possess a central column of differentiated keratinocytes expressing Keratin 79 (K79), which marks the future hair follicle opening. Here, we report that during late embryogenesis and early postnatal development, K79+ cells at the distal tips of these columns downregulate E-cadh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…We have previously shown that nascent hair buds generate and extend columns of K79+ differentiated cells out into the epidermis, which subsequently undergo remodeling to form hair follicle openings. 39 , 43 In embryonic (E) day 16.5 skin, we observed K79+ columns in developing hair buds, as expected, but no PPARγ expression ( Figure 1F ). By E17.5, however, we noticed basal PPARγ expression, reminiscent of the K5+PPARγ+ transitional basal cells seen in adult follicles ( Figure 1F ).…”
Section: Resultssupporting
confidence: 82%
“…We have previously shown that nascent hair buds generate and extend columns of K79+ differentiated cells out into the epidermis, which subsequently undergo remodeling to form hair follicle openings. 39 , 43 In embryonic (E) day 16.5 skin, we observed K79+ columns in developing hair buds, as expected, but no PPARγ expression ( Figure 1F ). By E17.5, however, we noticed basal PPARγ expression, reminiscent of the K5+PPARγ+ transitional basal cells seen in adult follicles ( Figure 1F ).…”
Section: Resultssupporting
confidence: 82%
“…Concordantly, studies in ichq mice, which develop ichthyotic features due to a mutation in Cst6 , have also found that disease onset coincides with the emergence of hair 49,50 . These and other findings support the notion that the formation of the hair canal—an event characterized by extensive cellular remodeling, as well as shifts in immune and microbial composition—represents a seminal but also potentially vulnerable event in skin development 19,51,52 .…”
Section: Discussionsupporting
confidence: 78%
“…These and other findings support the notion that the formation of the hair canal-an event characterized by extensive cellular remodeling, as well as shifts in immune and microbial composition-represents a seminal but also potentially vulnerable event in skin development 19,51,52 .…”
Section: Discussionsupporting
confidence: 78%
“…In the mature HF, keratin (KRT)79+ cells line the inner surface of the infundibulum. 60,103 These general developmental stages occur during the morphogenesis of all hair types, but it has been shown in mice and Cashmere goats that the induction of different HF types (eg, primary and secondary HFs) occurs at different embryonic stages (eg, mouse awl and auchene hairs at E16.5 and zig zag hair around P0) and that their development is tuned by the interplay of different molecules. 17,94 The disturbance of the finely tuned HF morphogenesis at any level may result in congenital alopecia.…”
Section: Hf Morphogenesismentioning
confidence: 99%